Patients’ Attitudes toward Student Nurses in a Surgical Ward of a Hospital in Nepalgunj: A Cross-Sectional Study - Dhakal, Sunita (Academia Research Journal, 2026)
Clinical training of nursing students in hospital settings is essential for developing competent professionals, yet patient attitudes toward their involvement can influence care quality, patient satisfaction, and the learning environment. In Nepal, where the nursing profession continues to face social stigma, understanding patient perceptions of student nurses remains understudied, particularly in district-level hospitals. This study aimed to assess the level of patients’ attitudes toward student nurses and to examine associations between these attitudes and selected socio-demographic variables among patients admitted to the surgical ward of Western Hospital, Banke District, Nepal. A descriptive cross-sectional design was employed. Using purposive sampling, 60 patients who had been exposed to student nurses for at least three days were interviewed using a structured questionnaire with a 5-point Likert scale (22 items; 14 positive and 8 negative statements). Data were analyzed using descriptive statistics (frequencies and percentages) and inferential statistics (chi-square test) with SPSS version 21. Attitude was classified as positive (>50% score) or negative (<50% score). The majority of respondents (61.7%) exhibited a negative overall attitude toward student nurses. While patients generally appreciated the grooming and neat appearance of students (95% positive responses), they expressed significant discomfort with repeated and prolonged examinations (76.7% negative), perceived limited knowledge among students (68.3% negative), and reluctance to have students involved in care (61.7% preferred no student presence). No statistically significant associations were found between overall attitude domains and most socio-demographic variables (age, sex, ethnicity, religion, education, occupation) at p < 0.05. Patients admitted to the surgical ward predominantly held negative attitudes toward student nurses, particularly concerning perceived competence and intrusiveness of involvement. These findings highlight the need for enhanced clinical preparation of students, improved communication skills training, and greater public awareness of the educational role of student nurses to optimize both patient experience and clinical learning outcomes in resource-limited settings.